Personality traits and marital quality among Muslims newly-weds in Selangor, Malaysia - Juhari, Rumaya; Sahrani, Syah Qurratu Aini; Mastor, Khairul Anwar (Australian Academy of Business and Social Sciences, 2014)
This cross-sectional study aims to examine the relationships between personal factors, personality and marital adjustment among individuals who have been married no longer than 24 months at the time of the study. A total of 549 respondents were recruited as respondents. A set of translated and pilot tested instruments were used in the self-administered questionnaire. Dyadic Adjustment Scale (Spanier, 1979), and Goldberg's Unipolar Big Five Markers (Saucier, 1994) were used to measure marital quality, and personality respectively. The findings revealed that 36.2% of the respondents reported low level of marital quality. While more than half of the respondents have average level of agreeableness, conscientiousness, emotional stability, openness and extraversion, more than onefourth of them reported low and very low level in the traits. Family income and educational background were found to be significantly related with marital quality. Multiple Regression Analysis indicated that conscientiousness and emotional stability significantly predicted a total of 22% variance of marital quality of the respondents. Apparently, newly-married individuals who have higher conscientiousness and more stable emotionally tend to have better marital adjustment. It can be implied that the role of personality that relates with one being attentive and caring, and emotionally stable is crucial in ensuring the adjustment process of the individuals at the early stage of marriage.